A25 Traffic stress and bicycling to elementary and junior high school: Evidence from Davis, California. Issue 2 (June 2015) - Fitch, Dillon; Thigpen, Calvin; Handy, Susan
Abstract: Background: A growing body of evidence shows that youth who walk or bike to school have higher levels of overall physical activity. In turn, greater physical activity is associated with lower incidence of chronic disease and better physical and psychological wellbeing. This association is especially important considering the increasing prevalence of obesity-related diseases (e.g. type II diabetes, cardiovascular disease), and the tracking of health from childhood to adulthood. Although the direct relationship between active travel to school and general measures of health is uncertain, it is reasonable to expect mostly positive effects of active travel on the health of youth. Indeed, at least one study has documented a relationship between bicycling to school and a more specific measure of health, cardiorespiratory fitness. In the U.S., where bicycling to school is uncommon, there is therefore an opportunity to improve health by increasing rates of bicycling to school. Previous research has identified several factors that influence bicycling to school, including (among others): access to bicycles, attitudes and perceptions about bicycling, parental encouragement, and distance/time from home to school. However, the influence of the urban environment on bicycling to school is not well studied in the U.S., and current evidence is inconsistent. This study examines the factors associated with bicycling to elementary and junior high school, with particular focus on the barrier of traffic safety as influenced by various roadway characteristics. Methods: his study examines the factors associated with bicycling to elementary and junior high school, with particular focus on the barrier of traffic safety as influenced by various roadway characteristics. We use data from repeated observations of bike rack counts at 10 neighborhood schools in Davis, California over the course of two years (2012 to 2014). We adopt the Bicycle Level of Traffic Stress (BLTS) methodology for estimating traffic stress (i.e. the likely stress imposed on a bicyclist by automobile traffic), and use Bayesian binomial multi-level (hierarchical) regression models to analyze the influence of traffic stress and other covariates on bike rack counts. Results: Our results indicate that in general, neighborhood schools with a greater proportion of surrounding homes with low-stress routes to school have greater rates of bicycling to school. Furthermore, model results indicate that the influence of strategic, low stress roadway improvements on bicycling to school rates is positive, even after accounting for other covariates (e.g. socio-demographics). Conclusions: These results suggest that increasing bicycle access to school should be considered as an important benefit when urban planners prioritize road improvements, and that BLTS-type metrics may be a suitable quantitative framework for designing safe routes to schools.